1995
DOI: 10.1177/000331979504600511
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Coronary Angioplasty for Culprit Lesions in Patients with Post Myocardial Infarction Angina Based on Dextrocardia and Anomalous Coronary Arteries

Abstract: Four cases of successful coronary angioplasty for anomalous coronary arteries, including dextrocardia associated with three-vessel disease, single left coronary artery with proximal left anterior descending lesion, anomalous right coronary artery (RCA) from adjacent left coronary sinus of Valsalva associated with proximal RCA lesion, and anomalous left circumflex angulated lesion bifurcated from the RCA, were encountered. Four cases with 8 target lesions who had a mean age of 63.5 +/- 11.5 years old are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…This coincides with the unexpectedly high incidence of anomalies reported here. We have not found any case of coronary arteries arising from the noncoronary (nonfacing) aortic sinus, or from one of the pulmonary sinuses, as has been reported in humans (Yabe & Tsukahara, 1995 ;Shanoudy & Russell, 1996). The possibility that we have missed such an abnormal origin is unlikely.…”
Section: mentioning
confidence: 41%
See 2 more Smart Citations
“…This coincides with the unexpectedly high incidence of anomalies reported here. We have not found any case of coronary arteries arising from the noncoronary (nonfacing) aortic sinus, or from one of the pulmonary sinuses, as has been reported in humans (Yabe & Tsukahara, 1995 ;Shanoudy & Russell, 1996). The possibility that we have missed such an abnormal origin is unlikely.…”
Section: mentioning
confidence: 41%
“…: j34 942 201924 ; fax : j34 942 201903 ; e-mail : icardojm!unican.es 1999). Coronary anomalies, however, occur when the heart is abnormally located, or in the presence of abnormal venoatrial connections, although the number of cases reported is very small if there are no associated intracardiac malformations (Topaz et al 1992 ;Yabe & Tsukahara, 1995 ;Shanoudy & Russell, 1996 ;Turchin et al 2000). The rarity of these situations has precluded the analysis of large samples.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have employed an AL1 guide [1,2]. From the radial approach we found that Judkins catheters were not useful and that an extra backup guide was most satisfactory.…”
Section: Clinical Casementioning
confidence: 87%
“…Some authors have chosen to use horizontal (right to left) image reversal during image processing so that the images obtained are effectively normalised [1]. We simply used equivalent right-sided views to produce the usual left-sided images and vice versa.…”
Section: Clinical Casementioning
confidence: 99%